2022
DOI: 10.3390/coatings12070964
|View full text |Cite
|
Sign up to set email alerts
|

Management of Teeth Affected by Molar Incisor Hypomineralization Using a Resin Infiltration Technique—A Systematic Review

Abstract: In recent years, an increase in children diagnosed with molar incisor hypomineralization (MIH) has been observed. Children with MIH show a high failure rate with conservative treatment. The ICON® system (DMG, Hamburg, Germany), which is an infiltration of decalcified lesions with resin, may strengthen the tooth structure, improve its aesthetics, and cure hypersensitivity. The following article is a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The use of infiltrants for masking enamel discolourations in hypomineralized teeth has spread more recently [ 9 ]. We evaluated the qualitative and quantitative clinical outcomes of resin infiltration on teeth with MIH for 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of infiltrants for masking enamel discolourations in hypomineralized teeth has spread more recently [ 9 ]. We evaluated the qualitative and quantitative clinical outcomes of resin infiltration on teeth with MIH for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that this high fluorescence is due to bacterial porphyrins in the carious lesion [ 15 , 17 ]. In MIH, opacities structure differs from caries etiology [ 9 , 18 ]. DIAGNOdent readings were recorded high in tooth with irregular enamel structure without dental caries as MIH [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RI was also used in the management of anterior teeth with MIH [ 91 , 92 ]. Earlier studies by Kim et al [ 93 ] found that the MIH teeth treated with RI showed significant colour changes after one week of treatment.…”
Section: Present: Clinical Usage and Limitations Of The Current Rimentioning
confidence: 99%
“…Molar incisor hypomineralisation (MIH) is a developmental defect that involves hypomineralisation of the enamel, most frequently targeting one or more of the first permanent molars and incisors ( Bulanda et al, 2022 ). The prevalence worldwide is increasing, along with other associated dental complications among these patients ( Almuallem and Busuttil-Naudi, 2018 ).…”
Section: Introductionmentioning
confidence: 99%